KEPEMIMPINAN, PENGHARGAAN, MOTIVASI DAN KEDISIPLINAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN RUMAH SAKIT - Daryono, Daryono; Istiatin, Istiatin; Sudarwati, Sudarwati (STIE PENA, 2025)
This study aims to determine and explain the influence of leadership, rewards, motivation and discipline on the Work Productivity of Employees at Sarila Husada Hospital Sragen. The population of this study was 200 employees of Sarila Husada Hospital Sragen with a sample of 35 people using a simple random sampling method. Data collection using a questionnaire. Data analysis techniques using the Multiple Linear Analysis method. The results of the study showed that leadership, rewards, motivation and discipline had a positive and significant effect by contributing to productivity by 81.8% while the remaining 18.2% was explained by other variables not proposed in this study. Suggestions from this study, employees of Sarila Husada Hospital Sragen can improve motivation and discipline in leadership that provides awards in accordance with work results in order to increase productivity in the hospital.Keywords: Productivity, Leadership, Awards, Motivation, Discipline, Employees